2015
DOI: 10.1053/j.gastro.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nicotinamide Adenine Dinucleotide Phosphate Reduced Oxidase 4 Regulates Stress Signaling, Fibrosis, and Insulin Sensitivity During Development of Steatohepatitis in Mice

Abstract: Background & Aims Reactive oxidative species (ROS) are believed to be involved in the progression of non-alcoholic steatohepatitis (NASH). However, little is known about the sources of ROS in hepatocytes or their role in disease progression. We studied the effects of NADPH oxidase 4 (NOX4) in liver tissues from patients with NASH and mice with steatohepatitis. Methods Liver biopsy samples were obtained from 5 patients with NASH, as well as 4 patients with simple steatosis and 5 patients without steatosis (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
159
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 55 publications
(74 reference statements)
10
159
3
1
Order By: Relevance
“…In addition, it will be of interest to feed alcohol to mice with hepatocyte-specific deletion of NOX4. Previous study showed that hepatocyte-specific deletion of NOX4 attenuated oxidative stress, lipid peroxidation, and liver fibrosis in mice with dietary induced steatohepatitis 36 . Thus, mice with hepatocyte-specific deletion of NOX4 may protect from alcohol-induced liver injury via decrease of oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it will be of interest to feed alcohol to mice with hepatocyte-specific deletion of NOX4. Previous study showed that hepatocyte-specific deletion of NOX4 attenuated oxidative stress, lipid peroxidation, and liver fibrosis in mice with dietary induced steatohepatitis 36 . Thus, mice with hepatocyte-specific deletion of NOX4 may protect from alcohol-induced liver injury via decrease of oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…23 Moreover, the presence of p47phox in liver parenchymal cells has also been shown to be a key mediator of liver pathology in alcoholic liver disease. 24 In addition, recent studies from Bettaieb et al 25 suggest that hepatocyte Nox4 may also play an important role in development of oxidative stress and progression of NASH pathology to inflammation and fibrosis. In the current study, knockdown of Ppara also resulted in increased inflammation, necrosis, matrix remodeling, and evidence of stellate cell activation and fibrosis after feeding 70% HF diets relative to Wt mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a wide array of evidence shows that Nox4-derived reactive oxygen species play a major role in the pathogenesis of renal, cardiac, lung, and liver fibrosis (9,36,37,40,45,49,63,65). Importantly, Nox4 has also been reported to be a primary target of TGF-␤ and a critical mediator of its profibrotic actions in various cell types (7,36,40,45).…”
Section: Effect Of Gadolinium-based Contrast On Fibroblasts In Vitromentioning
confidence: 99%
“…Importantly, Nox4 has also been reported to be a primary target of TGF-␤ and a critical mediator of its profibrotic actions in various cell types (7,36,40,45). It should be pointed out that pharmacological inhibitors of Nox4 are available and have undergone preclinical studies in animal models of fibrotic diseases, where they successfully attenuated the pathological changes observed in renal complication of diabetes, atherosclerosis, liver fibrosis and idiopathic pulmonary fibrosis (5,9,36,37,40,49,50,63). Therefore, Nox4 may represent an attractive therapeutic target for prophylaxis or the treatment of gadolinium-associated systemic fibrosis.…”
Section: Effect Of Gadolinium-based Contrast On Fibroblasts In Vitromentioning
confidence: 99%